Screenwriting: a strategy for the improvement of writing instructional practices (2010)
This article presents a pedagogical experience that addresses the use of an instructional strategy called screenwriting aimed at improving the teaching of writing in an educational context. This pedagogical intervention took place in a private English language school, where three adult students willingly participated to create their own short scripts. The idea was to introduce and reinforce the importance of screenwriting to observe its usefulness in education. Students participated in writing workshops for a 3-month period. The workshops included the respective screenwriting theory and activities that helped them to achieve completion of their final stories. Students’ final pieces proved that the writing instructional practices were enriching and beneficial. En este artículo se presenta una experiencia pedagógica sobre el uso de una estrategia instruccional llamada "la escritura de guiones", y cuyo objetivo es mejorar la enseñanza de la escritura en un contexto educativo. Esta intervención pedagógica tuvo lugar en una institución privada, dedicada a la enseñanza de lengua inglesa, donde tres estudiantes adultos participaron en la creación de sus propios guiones cortos. La idea era introducir y reforzar la importancia de la escritura de guiones para observar su utilidad en la educación. Los estudiantes participaron durante tres meses en talleres de escritura creativa. Estos incluyeron teoría y actividades para la escritura de guiones respectivos que los ayudaron a lograr sus historias finales. Los trabajos finales de los estudiantes mostraron que las prácticas instruccionales de escritura fueron enriquecedoras y benéficas.